Temperature charts of Hevea brasiliensis during log steaming and its effect on the board cracks - Pelozzi, M. M. A. [UNESP]; Severo, Elias Taylor Durgante [UNESP]; Rodrigues, P. L. M. [UNESP]; Calonego, F. W. [UNESP] (Springer, 2014)
The temperatures of Hevea brasiliensis logs during the steaming process were determined and correlated with the cracks of the boards. Thermocouples were inserted at the center of the logs, and the temperatures were recorded inside the material during steaming at 54, 75 and 92 A degrees C. Logs were cut and the cracks of the boards were measured. The results showed that: (1) the sigmoidal logistic model explains the variation of temperature in the logs; (2) the variation in the length of cracks between the peripheral boards and those taken near the pith were 194.6, 150.6 and 138.8 % for the material steamed at 54, 75 and 92 A degrees C, respectively; and (3) the board's cracks were smaller in the logs that reached the glass transition temperature. A chart to determine the steaming logs time as a function of the steam temperature and the desired temperature inside Hevea brasiliensis logs was developed.